2016
DOI: 10.14419/ijet.v5i3.5984
|View full text |Cite
|
Sign up to set email alerts
|

Review on experimental study of Nd:YAG laser beam welding, with a focus on aluminium metal matrix composites

Abstract: The demand for high performance materials particularly in aviation and automobile industries gradually increases, CO 2 and Nd: YAG lasers are becoming most popular in processing these advanced materials. In this context, one of the most important process is joining by welding. It has been a constant endeavour by researchers to explore various methods and techniques to enhance the process efficiency of autogenous Nd: YAG laser welding of various materials i.e. without any filler materials. In this work, we pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…That is, Taguchi considers experimental design as a means for reducing the sources of variation on process or product quality characteristics. 33 Taguchi method employs the orthogonal arrays to study a large number of variables by conducting a small number of experiments. The conclusion results extracted from small-scale experiments are reliable over the entire experimental region.…”
Section: Taguchi Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, Taguchi considers experimental design as a means for reducing the sources of variation on process or product quality characteristics. 33 Taguchi method employs the orthogonal arrays to study a large number of variables by conducting a small number of experiments. The conclusion results extracted from small-scale experiments are reliable over the entire experimental region.…”
Section: Taguchi Methodsmentioning
confidence: 99%
“…Taguchi's orthogonal array is simple to use because it presents the experimental design in a table and the results are given in the form of linear graphs. 33 Taguchi proposed the concept of signal-to-noise (S/N) ratios to be used as measures of the effect of noise factors on target characteristics. In this work, the weld width has been considered as smallerthe-better type, whereas the weld penetration is of the higher-the-better type.…”
Section: Taguchi Methodsmentioning
confidence: 99%
“…Moreover, the authors showed that increasing the SiC content from 0 to 20% caused a decrease in the reflection of the laser beam and an increase in melt viscosity. This was potentially caused by an increasing amount of Al 4 C 3 compound [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the obtained SiCp/AMCs joints may have a poor appearance, severe segregation of SiC particles, and degradation of mechanical performance. Laser welding was recognized as a more ideal substitution over other traditional welding method due to its higher energy density, larger productivity and narrower heat affected zone (Chao et al, 2013;Banerjee et al, 2016). Extensive efforts have been devoted to explore the appropriate processes in order to obtain a laser welded SiCp/AMCs joints with satisfactory weld formation.…”
Section: Introductionmentioning
confidence: 99%